Genetic variability, correlation and path coefficient analysis for yield and yield components of selected lentil (Lens culinaris M.) genotypes - Chowdhury, Md Mahmuduzzaman; Haque, Md Ashraful; Malek, Md Abdul; Rasel, Md; Ahamed, Kamal Uddin (Fundamental and Applied Agriculture, 2019)
Genetic variability, correlation coefficient and path coefficient were estimated for different morpho-physiological traits of 20 lentil genotypes. A significant genetic variation was observed for all the observed traits. Significantly higher PCV values than those of GCV for all the traits indicated that the traits are more influenced by the environment. The highest estimates of GCV and PCV were observed for seed yield plant−1 (23.80% and 24.03%, respectively) followed by number of pods peduncle−1 (16.91% and 19.80%, respectively). All the studied traits expressed high heritability ranging from 64.89% to 98.46% and the maximum was recorded for seed plant−1 (98.46%) followed by pod plant−1 (98.35%) and seed yield plant−1 (98.10%). High heritability along with high genetic advance was noticed for number of pods plant−1 (98.35% and 50.63, respectively) and number of seeds plant−1 (98.46% and 96.01, respectively) and high heritability coupled with high genetic advance as per cent of mean was observed for number of seeds plant−1 (98.46%, 39.80%) followed by number of pods plant−1 (98.35%, 33.03%) reflected the accumulation of additive gene and phenotypic selection for these characters will be effective for seed yield improvement. The study of associations among the different traits revealed that seed yield plant−1 was significantly and positively correlated with number of primary branches plant−1, pods plant−1 and seeds plant−1 and 100-seed weight. Path analysis also reported that number of pods plant−1, seeds pod−1 and 100-seed weight was related to the seed yield mostly through the direct positive effect. So, the traits viz., number of primary branches plant−1 and pod plant−1 and 100-seed weight should get the major importance during traits selection for lentil yield improvement as those traits had positive and significant correlation as well as direct positive effect with seed yield plant−1 and the information of wide genetic diversity for this traits could be used in future systematic lentil breeding programs for the improvement of seed yield.